2013
DOI: 10.1002/mas.21367
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of hydrazine derivatives for mass spectrometric analysis of carbohydrates

Abstract: Over the last years, extensive studies have evaluated glycans from different biological samples and validated the importance of glycosylation as one of the most important post-translational modifications of proteins. Although a number of new methods for carbohydrate analysis have been published and there has been significant progress in their identification, the development of new approaches to study these biomolecules and understand their role in living systems are still vivid challenges that intrigue glycobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 106 publications
(154 reference statements)
1
48
0
3
Order By: Relevance
“…23,28 In the spectra of glycoproteins isolated from species Solanum andigenum and Solanum stenotomum, additional peaks appeared at m/z 1671.6 and 1833.7 (Figure 1c). Tandem mass spectra showed that these N-glycans had both antennae occupied with hexose residues only, and the fragmentation pattern was similar to that assigned to high-mannose structures as previously described.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 93%
“…23,28 In the spectra of glycoproteins isolated from species Solanum andigenum and Solanum stenotomum, additional peaks appeared at m/z 1671.6 and 1833.7 (Figure 1c). Tandem mass spectra showed that these N-glycans had both antennae occupied with hexose residues only, and the fragmentation pattern was similar to that assigned to high-mannose structures as previously described.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 93%
“…A review on the use of hydrazine derivatives for the mass spectrometry of carbohydrates has been written by Lattová and Perreault () (104 cited references). Derivatization of carbohydrates as hydrazides ( 49 ) has been achieved in as little as 5 min.…”
Section: Derivativesmentioning
confidence: 99%
“…Thus, the analysis of glycosylation is extensively conducted in biological and clinical research as well as in pharmaceutical industry [8][10]. Different methods have been reported, including high performance liquid chromatography (HPLC) [11], [12], capillary electrophoresis [13], [14] and high pH anion-exchange chromatography [15], [16] with electrochemical, optical or mass spectrometric (MS) detection [17], [18]. To enhance the detection sensitivity, oligosaccharides are usually derivatized prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the detection sensitivity, oligosaccharides are usually derivatized prior to analysis. Most of such derivatization reactions can be accomplished by coupling the reagents with the reducing end of saccharides [17], [19]. During this step, reagents, including salts, derivatization reagents and solvent are normally presented in large excess.…”
Section: Introductionmentioning
confidence: 99%